Titanium dioxide nanoparticles and nanotubular surfaces: Potential applications in nanomedicine - Ribeiro, Ana Rosa [UNESP] (2017)
Titanium dioxide nanotubes and nanoparticles are believed to be stable, possess antibacterial properties, and biocompatible and less toxic than other nanostructures, making them excellent candidates for biomedical applications. Among others, they have been widely used as drug-delivery systems, components for articulating orthopaedic implants or cosmetics for dermatological and skin lesion treatments. However, when exposed to the biological environment, selective proteins and ions may adsorb to the nanostructures creating a dynamic nano-bio interface that mediate a cellular response. This complex nano-bio interface depends on the physical-chemical characteristics of the nanostructures as well as the specific biological environment. In this chapter, the formation of these biocomplexes (protein and ions) is discussed together with its impact on cellular behaviour. Finally, the potential application of TiO2 nanoparticles and nanotubes in nanomedicine will be addressed.